2015
DOI: 10.1016/s0140-6736(14)61886-9
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical versus manual chest compression for out-of-hospital cardiac arrest (PARAMEDIC): a pragmatic, cluster randomised controlled trial

Abstract: National Institute for Health Research HTA - 07/37/69.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
279
4
27

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 397 publications
(315 citation statements)
references
References 26 publications
5
279
4
27
Order By: Relevance
“…[8] The population reported in this trial is larger than that reported in the PARAMEDIC trial as it includes patients assessed during the set up phase of the trial. The PARAMEDIC trial was registered on the International Standard Randomised Controlled Trial Number Registry (ISRCTN08233942) and received ethical approval from Coventry Resarch Ethics Committee: 09/H1210/69.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[8] The population reported in this trial is larger than that reported in the PARAMEDIC trial as it includes patients assessed during the set up phase of the trial. The PARAMEDIC trial was registered on the International Standard Randomised Controlled Trial Number Registry (ISRCTN08233942) and received ethical approval from Coventry Resarch Ethics Committee: 09/H1210/69.…”
Section: Methodsmentioning
confidence: 99%
“…[8] The trial utilised 91 ambulance stations across four UK National Health Service (NHS) Ambulance Services. Ambulance vehicles were randomized to deliver manual cardiopulmonary resuscitation (CPR) or the LUCAS-2 device (Lund University Cardiopulmonary Assistance System) to eligible patients.…”
Section: Settingmentioning
confidence: 99%
“…For the purpose of this review, we measured the baseline (or first) time point for describing healthrelated quality of life as reported by individual studies; conventionally in trial-based economic evaluations this is taken as the time of randomisation. Nine (47%) of the 19 studies used the EQ-5D to measure health-related quality of life of patients, 5 (26%) used the EQ-5D in combination with another instrument (primarily the SF-12/36 [26,33,35], HUI-3 [32] and the paediatric PedsQL [36]), 1 (5%) [18] used the 15D instrument [34] and another 1 (5%) used the HUI-3 [28]. The remaining 3 (17%) studies [29] [25,27] did not report a primary health-related quality of life data collection process.…”
Section: Measurement Of Health-related Quality Of Lifementioning
confidence: 99%
“…The most obvious limitation is that it is not possible to obtain direct estimates from deceased or permanently incapacitated patients (who would not be missing at random). For example, in the PARAMEDIC 1 trial [35], only 6.6% of 1471 individuals experiencing out-of-hospital cardiac arrest recruited into the trial survived to 3 months post arrest, the first time point at which health-related quality of life data were collected. Asking patients to retrospective recall their baseline health-related quality of life would not be an option for the majority of this trial's participants.…”
Section: Retrospective Recall Of the Baseline Health-related Quality mentioning
confidence: 99%
“…16,17 Conventional manual chest compressions remain the standard of care for the treatment of cardiac arrest, but mechanical chest compression devices may be a reasonable alternative for use by properly trained personnel. [18][19][20] When rapidly implemented, extracorporeal cardiopulmonary resuscitation (ECPR) can prolong viability for patients who are not resuscitated with conventional CPR. ECPR can provide time to treat potentially reversible conditions or arrange cardiac transplantation.…”
Section: Advanced Life Support-adultmentioning
confidence: 99%